Three-dimensional surface fatigue crack growth life assessment model of steel welded joints and structures. Issue 8 (June 2022) - Fang, Zhao; Li, Aiqun; Ding, Youliang; Shen, Sheng
To investigate the fatigue crack growth of surface cracks in steel welded joints, a three-dimensional surface fatigue crack growth life assessment model considering both the surface crack growth period and the following through crack growth period is proposed. The fatigue crack growth life of a standard steel butt joint specimen is predicted considering the effect of welding residual stress and it is compared with fatigue test results. An example of a welded beam-to-column connection in a steel high-rise building under wind is selected to demonstrate the improvement of the model to make it applicable to stochastic loading and real engineering structures. The life results are compared with those obtained by other fatigue assessment approaches. The mesh sensitivity analysis is made and the effect of extreme welding imperfections and corrosion environment are both discussed. Guidance to select the fatigue life assessment approaches is also proposed. The results show that the growth shape of the edge crack remains a quarter of a circle while that of the center crack remains a quarter of an ellipse during the growth; When the surface crack grows through the plate thickness and becomes a through crack, the remaining fatigue crack growth life is unneglectable for real engineering components especially for the ones with a large plate width; The effect of welding residual stress on the fatigue crack growth life of real engineering component is complex and it depends on the distribution of the residual stress itself; The proposed three-dimensional surface crack engineering model can acquire accurate life results and is applicable to stochastic loading and engineering structures.